2008
DOI: 10.1513/pats.200707-114mg
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Adult Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is a common disorder characterized by repetitive narrowing or collapse of the pharyngeal airway during sleep. The disorder is associated with major comorbidities including excessive daytime sleepiness and increased risk of cardiovascular disease. The underlying pathophysiology is multifactorial and may vary considerably between individuals. Important risk factors include obesity, male sex, and aging. However, the physiological mechanisms underlying these risk factors are not clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
321
0
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(374 citation statements)
references
References 148 publications
(149 reference statements)
6
321
0
16
Order By: Relevance
“…Nevertheless, a clear increase in the PSDn of SAHS-positive subjects can be observed in the range 0.015-0.060 Hz, covering part of VLF and LF bands (see Figure 3). It has been established that the typical duration of apnoeic events ranges from 20 to 40 s [45], which in the frequency domain would mainly affect the 0.025-0.050 Hz band. Latest studies confirmed this as the band with the highest statistically significant differences between SAHSpositive and SAHS-negative subjects in the airflow signal [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a clear increase in the PSDn of SAHS-positive subjects can be observed in the range 0.015-0.060 Hz, covering part of VLF and LF bands (see Figure 3). It has been established that the typical duration of apnoeic events ranges from 20 to 40 s [45], which in the frequency domain would mainly affect the 0.025-0.050 Hz band. Latest studies confirmed this as the band with the highest statistically significant differences between SAHSpositive and SAHS-negative subjects in the airflow signal [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The principal mechanism has been attributed to recurrent collapse of pharyngeal airway during sleep, causing intermittent blood-gas disturbance (hypercapnia and hypoxemia) and surges of sympathetic activation 11 .…”
Section: Mechanismmentioning
confidence: 99%
“…22 Obesity has also been implicated in anatomical changes that predispose patients to upper airway obstruction and reduced neuromuscular control of the air passages during sleep. 23,24 Obesity accelerates the initial onset and progression of physical disability in older adults. 25 Maternal obesity is associated with an increased risk for congenital anomalies.…”
Section: Us Endocrinologymentioning
confidence: 99%